P2.107 Atopic Dermatitis in a HIV-Positive Cohort at Ruhr University Bochum. (13th July 2013) - Tigges, C; Fuchs, W; Potthoff, A V; Brockmeyer, N H
Abstract : Background: In HIV-positive individuals clinicians observe a broad range of skin conditions like xerosis, tumours, rash and drug-induced exanthema as well as common skin infections caused by bacteria, fungi and viruses. Beyond this, some reports point out a higher incidence on atopic conditions like atopic dermatitis (AD), sinusitis, asthma and laboratory findings like hypereosinophilia and Hyper IgE. Methods: Between May and November 2006, 196 patients of the HIV outpatient department of the Clinic for Dermatology, Venerology and Allergology at the Ruhr University Bochum underwent a dermatological examination. Skin conditions focusing on AD were measured by SCORAD (SCORing Atopic Dermatitis) and Erlanger atopy score. Results: In general, 36 patients (18.4%) out of 196 participants suffered from clinically from AD. Median count at "Erlanger Atopy Score" was 12.8 (median 11.5). Verification by SCORAD showed 55.6% (20/36) with mild, 36.1% (13/36) with moderate and 8.3% (3/36) with severe AD. Neither with pruritus and viral load nor with CDC Category a correlation was found. Exclusively CD4 counts were negative correlated with higher Visual analogue scale for prutitus (p = 0.0306). Xerosis was diagnosed in more than 53.6% of the 196 patients and thus was the leading diagnosis, although there was no correlation with the CD4 count, viral load or CDC Category. Furthermore, a negative correlation was found (p = 0.0214) between IgE and CD4 and a p-value of 0.0111 between IgE and the CDC Category (higher IgE, higher CDC Category) was demonstrated as well. Conclusion: In our sample xerosis cutis was the leading diagnosis. Furthermore, compared to pre-existing literature for the first time standardised diagnostic tools for AD, the SCORAD and the Erlanger Atopy Score, were used to examine HIV-positive individuals. Diagnostic tools help to identify the origin of dry skin in HIV-infected patients and to initiate adequate treatment.